Assessment of a novel hysteretic friction damper for the seismic retrofit of reinforced concrete frame structures. (December 2022) - Bruschi, Eleonora; Quaglini, Virginio
Abstract: In this paper, a novel hysteretic friction damper, called Prestressed LEad Damper with Straight Shaft (or PS-LED), is presented as a viable solution for the seismic rehabilitation of existing RC framed buildings. The PS-LED is characterized by high stiffness and damping capability combined with a compact design, and low manufacturing cost, which make it suitable for social housing. The constitutive behavior of the PS-LED, assessed experimentally in cyclic tests at different speeds, is formulated in the OpenSees framework through a simple rheological model comprising a parallel of a non-linear spring and a viscous model. To explore the viability of the PS-LED for seismic upgrade of existing buildings, a numerical investigation is performed by considering a RC frame structure, paradigmatic of a category of Italian buildings designed according to outdated codes. The case-study structure retrofit is designed considering two possible damage targets: (i) in the first case, the upgrade is performed in order to achieve elastic response of the structure under the basic design earthquake; (ii) in the second case, a partially dissipative behavior of the RC frame is conceived, with activation of plastic hinges to a repairable level. Non-linear static and Non-linear dynamic analyses are performed, showing a satisfactory agreement between the seismic performance and the design targets. As final stage, a comparison between two retrofit solutions with either the PS-LED or with a conventional steel hysteretic damper (SHD) is performed, demonstrating that the PS-LED, thanks to its high damping capacity, is able to control the increase in internal forces that usually affects frames upgraded with SHDs.